Estrategia didáctica en clases multitudinarias de matemática: opinion es de los alumnos - González de Galindo, Susana (2012)
A guide made according to the constructive approach about the contents of Differential Calculus was used in mass theoretical classes of Mathematics I, a first year subject of the School of Science, in order to overcome the traditional classes. The chosen model of learning was based on structural cognitive theories. The guide was created in order to provide a more interactive strategy, so as to be completed with students´ reflections. The chosen activities aimed to stimulate the problems, the formulation of hypothesi,s and the connection among contents in order to achieve significant learning. A survey performed to students was analyzed for evaluation of the experience. As a conclusion, most of the students would be in favor of the application of the new methodology on the whole subject.